2011
DOI: 10.1007/s00464-011-2039-9
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic ultrasound-guided endoscopic necrosectomy of the pancreas: is irrigation necessary?

Abstract: Neither endoscopic nor external flushing is needed for successful endoscopic treatment of symptomatic necroses. Even without irrigation, the outcome for patients treated with endoscopic necrosectomy is comparable to that described in the published data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(11 citation statements)
references
References 18 publications
(34 reference statements)
0
10
0
1
Order By: Relevance
“…The largest study, which included 639 patients from the Netherlands, reported that the predominant cause of necrotizing pancreatitis was biliary factors (48%), followed by alcohol consumption (24%), and unknown factors (19%) . Based on our review of the literature, the leading causes of acute pancreatitis resulting in WON were biliary factors (median 40%, range 14–81%), alcohol consumption (median 27%, range 2–70%), and idiopathic factors (median 14%, range 4–45%) …”
Section: Consensus Statementsmentioning
confidence: 98%
“…The largest study, which included 639 patients from the Netherlands, reported that the predominant cause of necrotizing pancreatitis was biliary factors (48%), followed by alcohol consumption (24%), and unknown factors (19%) . Based on our review of the literature, the leading causes of acute pancreatitis resulting in WON were biliary factors (median 40%, range 14–81%), alcohol consumption (median 27%, range 2–70%), and idiopathic factors (median 14%, range 4–45%) …”
Section: Consensus Statementsmentioning
confidence: 98%
“…External drainage can be used for monitoring adequate drainage and for irrigation. However, no studies have demonstrated the efficacy of external drainage . Given the discomfort associated with a nasocystic tube, routine use cannot be recommended.…”
Section: Resultsmentioning
confidence: 99%
“…However, no studies have demonstrated the efficacy of external drainage. 25 Given the discomfort associated with a nasocystic tube, routine use cannot be recommended. Multiple gateway 26 or dual modality 27 (combined percutaneous and endoscopic drainage) techniques may be viable alternatives.…”
Section: Quality Of Evidence: Ii-3mentioning
confidence: 99%
“…An über 100 Patienten mit Zysten und Nekrosen wurde auf einem Poster gezeigt, dass eine über die transmurale Drainage in den Gastrointestinaltrakt hinausgehende zusätzliche Spülbehandlung ohne signifikanten Einfluss auf den weiteren Verlauf ist [38]. Zum gleichen Schluss kam unserer Arbeitsgruppe in einer Arbeit, die in diesem Jahr publiziert wurde [39]. Mehrere Arbeiten beschäftigten sich mit der Anwendung von selbstexpandierenden Metallstents bei Pankreaszysten und nekrotisierender Pankreatitis.…”
unclassified